Profil Peresepan Obat Diabetes Melitus di RSUD Prof. Dr. H. M. Anwar Makkatutu Kab.Bantaeng Periode Agustus – Oktober 2022 - hayat, Nur; Herman, Hendra; Zulkarnain, Iskandar (PHARMACY UMI JOURNAL SYSTEM, 2023)
Diabetes mellitus (DM) is a progressive chronic disease characterized by the body's inability to metabolize carbohydrates, fats and proteins, causing hyperglycemia (high blood sugar). At Prof. Hospital Dr. H. M. Anwar Makkatutu Diabetes Mellitus is a disease that has the highest prevalence based on previous observations. The purpose of this study is to obtain data on prescribing profiles through administration screening, pharmaceutical screening and clinical screening on diabetes mellitus drugs given to patients at Prof. Hospital. Dr. H. M. Anwar Makkatutu, Bantaeng Regency for the period August-October 2022. The research method used is descriptive. The population used was all diabetes mellitus prescriptions (255 recipes) during the study period. Administrative screening showed that 100% of prescriptions did not include height. Pharmaceutical screening yielded 100% of prescriptions did not include instructions for using the drug. Clinical screening found potential drug interactions in 69 cases. Of the 69 cases of interaction that occurred, 89.86% were moderate. The conclusion of this study is the profile of diabetes mellitus drug prescribing in patients at Prof. Hospital. Dr. H. M. Anwar Makkatutu, Bantaeng Regency, has not met the standards of pharmaceutical services in hospitals.